2018
DOI: 10.3390/nu10040398
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Magnesium or Calcium and Chemotherapy-Induced Peripheral Neuropathy in Colorectal Cancer Patients

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and severe side-effect in colorectal cancer (CRC) patients. This study assessed the association between habitual dietary intake of magnesium or calcium and prevalence and severity of chronic CIPN in CRC patients receiving adjuvant chemotherapy. For this prospective cohort study, 196 CRC patients were considered. Magnesium and calcium intake was determined using a food frequency questionnaire at diagnosis, during and after chemotherapy. Chronic CIPN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Several drugs have been reported for treating CIPN. In these reports, calcium and magnesium, goshajinkigan, duloxetine, vitamin B12, pregabalin, and gabapentin were used [41][42][43][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. However, calcium/magnesium, goshajinkigan, and gabapentin were found to be ineffective at treating CIPN in the largest double-blind randomized controlled trials (RCTs) for each drug.…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs have been reported for treating CIPN. In these reports, calcium and magnesium, goshajinkigan, duloxetine, vitamin B12, pregabalin, and gabapentin were used [41][42][43][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. However, calcium/magnesium, goshajinkigan, and gabapentin were found to be ineffective at treating CIPN in the largest double-blind randomized controlled trials (RCTs) for each drug.…”
Section: Discussionmentioning
confidence: 99%
“…Higher magnesium intake in the diet is associated with a lower risk of colorectal tumors ( Wark et al, 2012 ). Prior research has demonstrated that high dietary magnesium intake may reduce the prevalence of chemotherapy-induced peripheral neuropathy and severity in patients with colorectal cancer ( Wesselink et al, 2018 ). Thus, eating magnesium-rich foods may be a new strategy for cancer prevention.…”
Section: Therapeutic Application Of Magnesium In Other Diseasesmentioning
confidence: 99%
“…The time until Common Terminology Criteria for Adverse Events (CTCAE v4.0) grade 2 or higher CIPN was not significantly different between these three groups ( p value = 0.3383). In a 2018 prospective study written by Wesselink et al 39) , daily dietary intake of Ca/Mg was evaluated in 196 colorectal cancer patients. In that study, daily dietary intake of Mg during chemotherapy was associated with a lower occurrence and severity of CIPN (occurrence ratio: 0.53, 95% confidence interval (CI) −1.95, −0.22) 39) .…”
Section: Drug Treatmentmentioning
confidence: 99%